Zakat Regulation Review: Badan Amil Zakat Nasional’s Regulation Review Concerning the Validity of BAZNAS Cianjur - Nugraha, Ahmad Lukman; Ridwan , Achmad; Athoillah, Mohamad Anton; Ridwan, Ahmad Hasan (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study examines the implementation of BAZNAS Regulation No. 1 of 2019, which governs the procedures for the appointment and dismissal of BAZNAS leaders at both the provincial and regency levels. The primary objective of this research is to provide strategic recommendations for evaluating the regulation, thereby fostering a shared understanding between regional authorities and BAZNAS RI. The study adopts a qualitative research methodology, employing a sociological legal approach. Data collection was conducted through observational studies at BAZNAS Cianjur. The findings reveal that the implementation of BAZNAS Regulation No. 1 of 2019 has resulted in divergent interpretations, particularly concerning the authority of regional heads in appointing BAZNAS leadership candidates. The Cianjur Government maintains that regional heads possess exclusive authority in this process, free from external influence, including that of BAZNAS RI. In response to these interpretational differences, this study proposes several recommendations to harmonize the appointment process. First, the selection procedure should include formal discussions between leadership candidates and regional heads. Second, regional heads should conduct an additional factual verification process and maintain records on prospective candidates. However, in cases where a candidate is deemed legally ineligible, BAZNAS RI retains the authority to disqualify the individual and issue a formal Letter of Consideration. Third, candidates for BAZNAS leadership should hold certification as amil zakat practitioners. Lastly, the profession of amil zakat should be formally integrated into the Indonesian National Work Competency Standards. These recommendations aim to enhance the clarity and effectiveness of regulatory implementation, thereby promoting a more structured and coherent approach to leadership appointment within BAZNAS.